Study of Factors of Personal Qualifications, Product Design, Quality and Services affecting Purchase Decision of Apple Products in Narathiwat Province - Wanseng, Nussaba; Faisuk, Pimprapai; Sreesuwan, Yupawadee; Suksai, Suphat (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
The objectives of this study were (1) to study personal factors of purchase decision Apple products, 2) to study product design factor and quality and services factors in purchasing Apple products, 3) to compare the differences of personal factors affecting the purchase decision and 4) to study the influence of product design and quality and service factors affecting purchase decision of Apple products. This quantitative research collected data from 400 people out of a total population of 648,426 living in Narathiwat province. The survey method was used with a closed-ended questionnaire which contained personal qualification information, product design information and information on quality and services. The online questionnaire was sent and gathered information via Facebook and Line. The results showed that the product design and quality and service factors were associated with purchase decision of customers at a high level. Genders, age group and education level differences had influence towards purchase decision, however, marital status, occupation and income did not correlate with purchase decision of Apple products. The research hypothesis testing revealed that the product design had influence on customers’ purchase decision; modern design, aesthetic appeal and its durability. The quality and services also influenced customers’ purchase decision since the quality of the products had a highly secure operating system which resulted in more efficient operation.